2017
DOI: 10.5114/jcb.2017.70677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dose volume parameters evaluated using three forward planning – optimization techniques in cervical cancer brachytherapy involving two applicators

Abstract: PurposeThis study is intended to compare dose-volume parameters evaluated using different forward planning- optimization techniques, involving two applicator systems in intracavitary brachytherapy for cervical cancer. It looks for the best applicator-optimization combination to fulfill recommended dose-volume objectives in different high-dose-rate (HDR) fractionation schedules.Material and methodsWe used tandem-ring and Fletcher-style tandem-ovoid applicator in same patients in two fractions of brachytherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The evolution of 3D planning from 2D planning resulted in the advent of volume-based HDR-BT planning, where the dose can be prescribed to the HR-CTV delineated by CT and/or MRI scans with close monitoring of OAR doses [ 7 , 8 ]. Accurate target and OAR delineation led to T&R and T&O based dose optimization techniques to create conformal plans by altering dwell times and dwell positions [ 34 , 35 , 36 ]. Several studies have shown the benefits of image-guided volume-based brachytherapy planning in gynecological malignancies compared to Point A-based plans [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of 3D planning from 2D planning resulted in the advent of volume-based HDR-BT planning, where the dose can be prescribed to the HR-CTV delineated by CT and/or MRI scans with close monitoring of OAR doses [ 7 , 8 ]. Accurate target and OAR delineation led to T&R and T&O based dose optimization techniques to create conformal plans by altering dwell times and dwell positions [ 34 , 35 , 36 ]. Several studies have shown the benefits of image-guided volume-based brachytherapy planning in gynecological malignancies compared to Point A-based plans [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chakrabarti et al . in their study included tandem in CTV contour on plan comparisons of different applicators [ 3 ]. Vivekanandan et al .…”
Section: Purposementioning
confidence: 99%
“…Recent studies have shown that the outer margins of tumors may be missed with HDR brachytherapy if the dose prescription is optimized to point A without three-dimensional (3D) image guidance, especially if the tumor has not regressed significantly at the time of brachytherapy. [28][29][30] Image-guided planning allows for better tumor localization and delineation with more accurate optimized planning Original research to improve dose inhomogeneity, especially in patients with bulky disease.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%